Pengaruh Financial Distress, Free Cash Flow, dan Earning Power terhadap Manajemen Laba - Ulvi Zuhrotul Faukha; Suwarno Suwarno (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
This study aims to analyze the effect of financial distress, free cash flow, and earning power on earnings management. The sample of this study was 17 mining companies listed on the Indonesia Stock Exchange (IDX) for the period 2018-2022. Data were taken from the company's financial statements using the purposive sampling method. The type of hypothesis testing used was the T-test (partial) with multiple linear regression analysis. The results showed that financial distress had a positive effect on earnings management, free cash flow had a negative effect on earnings management, while earning power had no effect on earnings management.